Prevalences and related factors of substances use in female aborigines in southern Taiwan - Yang, M S; Ko, Y C; Wen, J K (The Kaohsiung journal of medical sciences, 1996)
Alcohol use and betel quid chewing are common in aborigines in Taiwan. The aims of this study were to evaluate the patterns of drinking, smoking, betel quid chewing and to assess the related factors of the above substance use among female aborigines. Three hundred female Bunun aborigines aged between 17 and 50 years were recruited into this study via a stratified-random sampling. Subjects were interviewed at their homes by trained interviewers using a structured questionnaire. Prevalences of various substances use were estimated as follows: alcohol, 67.7%; betel quid chewing, 36.4%; smoking, 11.6%; and over-the-counter drugs, 8%. Related factors of substances use were analyzed by multiple logistic regression as follows. Alcohol use was significantly related to low educational level, where the spouse was a drinker and there was an attitude in favor of female drinking. Significant factors related to smoking were folk religion and where the spouse was a smoker. Significant factors related to betel chewing were low educational level, and where the spouse was a betel chewer, and poor knowledge about the adverse health effects of betel chewing. We also found women who consumed alcohol and chewed betel quid were significantly to show more external health locus control. About 80% of women recognized the adverse effects of alcohol consumption and smoking to pregnancy outcomes. Although they knew the harmful effects of substance use, only half of them stopped using these substances during their pregnancy. Health education on the harmful effects of alcohol, betel quid, and cigarettes, especially during pregnancy is essential in primary care.